Правові наслідки порушення акціонерним товариством порядку вчинення значного правочину - Карчевський, К. А.; Karchevskyi, K. A. (Право і безпека. - 2013. - № 4 (51). - С. 152-157, 2013)
З’ясовано наслідки порушення акціонерним товариством порядку вчинення значного правочину. Серед наслідків досліджено недійсність значного правочину та майнову відповідальність посадових осіб товариства. Зроблено висновок про те, що основним наслідком є саме недійсність значного правочину. Під час дослідження недійсності значного правочину проведено порівняння з іноземним законодавством та вирішено питання про віднесення цього правочину до нікчемних або заперечних правочинів. Зазначено, що значний правочин акціонерного товариства, вчинений із порушенням установлених вимог, є заперечним.

Setting of certain rules of conduct by the legislation is guaranteed by various measures of influence that directly emanates from the general concepts of the theory of law about the norm of law. Measures of the state influence include legal liability and other adverse consequences for the offender. Types and content of appropriate measures of influence depend on the type and nature of broken relations. Stated above fully concerns major transactions of a joint-stock company, which are concluded with the violation of fixed requirements. The objective of the paper is to clarify what kind of legal consequences may occur in the case when a joint-stock company does not follow established by the law order of concluding a major transaction. For settling the stated objective some tasks associated with fixing all possible consequences of breaking the order of concluding a major transaction are solved in the paper. These tasks are also associated with clarifying the ratio of various measures and determination of the main one, with defining the content of the main consequence, etc. The possible consequences are recognition of a transaction void; invalidity of the decisions adopted by a joint-stock company’s administration; compensation of losses while maintaining the validity of the transaction; termination of the contract, etc. It is concluded that the main consequence is the invalidity of a major transaction. While studying invalidity of a major transaction, the author made a comparison with foreign legislation and classified this transaction to worthless and negative transactions. Special attention is paid to the reasons of using negativity of major transactions. Taking into account international experience and appropriate stages of corporate legislation development and legislation about major transactions it is considered necessary to classify a major transaction of a joint-stock company, concluded with violations of legal requirements, as a negative transaction. This approach does not exclude the possibility of attributing major transactions that are concluded by other subjects (for example, agricultural cooperatives or stateowned enterprises) or in some cases (for example, in the proceedings in bankruptcy cases) to the worthless transactions. Implementation of insignificance in this case should be directed to the protection of property interests of employees, state, creditors of the debtor and other persons who are unable to control the activity of executive agencies or who are weaker and vulnerable members of the property turnover in economical or organizational sense and when the court appeal of a major transaction will interfere already initiated court or other similar procedures.

Выяснены последствия нарушения акционерным обществом порядка совершения крупной сделки. Среди последствий исследована недействительность крупной сделки и имущественная ответственность должностных лиц общества. Сделан вывод о том, что основным последствием является именно недействительность крупной сделки. При исследовании недействительности крупной сделки проведено сравнение с иностранным законодательством и решены вопросы об отнесении данной сделки к ничтожным или оспоримым сделкам. Отмечено, что крупная сделка акционерного общества, совершенная с нарушением установленных требований, является оспоримой.
Legal consequences of breaking the order of a major transaction by a joint-stock company
Правовые последствия нарушения акционерным обществом порядка совершения крупной сделки
Keywords: акціонерне товариство; значний правочин; майнова відповідальність; недійсність правочину; нікчемність правочину; заперечність правочину; joint-stock company; major transaction; property liability; invalidity of the transaction; worthless transaction; negative transaction; акционерное общество; крупная сделка; имущественная ответственность; недействительность сделки; ничтожность сделки; оспоримость сделки